2013
DOI: 10.1038/jid.2013.6
|View full text |Cite
|
Sign up to set email alerts
|

Vemurafenib Induces Senescence Features in Melanoma Cells

Abstract: A large proportion of human melanomas harbor a mutation leading to permanent activation of the serine/threonine kinase BRAF, and as a consequence, they have developed dependence on BRAF/mitogen-activated protein kinase signaling. Accordingly, BRAF inhibitors such as Vemurafenib show a good anti-tumorigenic effect on metastases with the BRAF(V600E) mutation. Although an initial period of sustained tumor regression is usually observed after Vemurafenib treatment, tumors often relapse at the same site, and apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 43 publications
(50 reference statements)
5
81
0
Order By: Relevance
“…The effect sizes described are in the range of relevant findings described in previous publications using this methodology (14). 31 P NMR analysis revealed no significant differences in the levels of measured 31 P-containing metabolites, including NTP and PCr, between control-and vemurafenib-treated samples ( Supplementary Fig. S2).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The effect sizes described are in the range of relevant findings described in previous publications using this methodology (14). 31 P NMR analysis revealed no significant differences in the levels of measured 31 P-containing metabolites, including NTP and PCr, between control-and vemurafenib-treated samples ( Supplementary Fig. S2).…”
Section: Resultssupporting
confidence: 70%
“…The bioenergetic status of treated cells, as assessed by 31 P NMR analysis of cellular NTP and PCr levels and bioluminescence-measured ATP/ADP, remained unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular senescence can be triggered by overexpression or activation of oncogenes [9], and the loss of oncogene-induced senescence effectors may lead to the development of malignant tumors [7,8]. Intrinsic senescence can also be induced by therapeutic intervention, and it has been demonstrated that different antitumor drugs, such as cyclophosphamide [10] or the BRAF inhibitor vemurafenib [11], drive cancer cells into permanent growth arrest. Recently, we and others described cytokine-induced senescence (CIS) as an extrinsic form of senescence.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this assay, treatment with a BRAF inhibitor and radiotherapy should only be considered in patients who do not exhibit an increased susceptibility for BRAF inhibitor associated radiosensitization in the tested cells of the normal tissue. [77][78][79] or initiation of apoptosis [80][81][82] and senescence [83] in BRAF V600E cancer cells mainly of melanocyte origin. Dasgupta et al [77] and Sambade et al [78] achieved a further reduction of clonogenic survival and spheroid invasion potential after X-irradiation of BRAF inhibitor treated BRAF V600E melanocytes, and both attributed to their findings to the additional G2-arrest induced by ionizing radiation.…”
Section: Radiosensitizing Effects Of Braf V600 Inhibitors In Normal Hmentioning
confidence: 99%